Impact of secondary flow on the single-phase flow in spiral microchannels: An experimental study. (September 2022) - Kong, Lingjian; Liu, Guangzhe
Spiral microchannels have a wide range of applications, such as microscale cooling, fluid mixing and particle sorting, in micro-fluidic devices. The flow characteristics of spiral microchannels play an important role in the design and operation of these devices. An experimental study of the laminar flow characteristics in spiral microchannels is conducted for different Reynolds numbers from 51 to 985. Microchannels have rectangular cross sections and follow Archimedean spiral pathways with different spiral and cross-section parameters. The results show that the pressure drop of the spiral microchannel increases with increasing spiral diameter and aspect ratio, but decreases with spiral pitch and hydrodynamic diameter. In addition, the effect of the spiral and cross-section parameters on pressure drop is evident at the high Reynolds number. Under the influence of additional friction caused by the secondary flow, the friction factor of the spiral microchannel is higher than that of the straight channel, and its value increases with the increase in curvature of the microchannel. The correlation of the Poiseuille number in the spiral microchannel is established on the basis of the experimental results, and 95.3% of the experimental data fall within the error band of ±18%.